Older people's attitudes towards their regular medicines - Bagge M; Tordoff J; Norris P; Heydon S (CSIRO Publishing, 2013)
INTRODUCTION: Many qualitative studies examine older people's attitudes towards their medicines. Often these studies focus on the topic of medicines adherence. In contrast, this study aims to explore the attitudes of older people, aged 75 years and older, towards their regular prescription and non-prescription medicines. METHODS: This study comprised two investigations of people aged 75 years and older. In the first investigation, 20 people were purposefully selected and interviewed, using an oral history approach, about their experiences of medicines over a lifetime. In the second investigation, 40 people were recruited from two internal medicine wards. Semi-structured interviews were undertaken with participants about their experiences of medicine changes after discharge from hospital. All 60 interviews were digitally recorded, transcribed verbatim, coded using NVivo and analysed thematically. FINDINGS: Participants disliked having to take prescription medicines, but the majority believed they were necessary. They also trusted their doctor's expertise regarding medicines. Most participants believed it was important to take their prescription medicines regularly, even if they sometimes forgot to take them. They were not anxious about possible side effects. Most participants aimed to limit the use of analgesics and non-prescription medicines which they perceived as unnecessary. CONCLUSION: Even taking into account participants' dislike of having to take prescription medicines, they were willing to accept medicines as part of their everyday routine, as they believed they were necessary. This suggests that many older people may be more willing to take their medicines than some studies on adherence in the wider population have indicated.